Pertimbangan Hakim dalam Penetapan Dispensasi Nikah di Pengadilan Agama Kraksaan - Imam Syafii (UNIVERSITAS BONDOWOSO, 2021)
Marriage dispensation is legal assistance from the Religious Courts to prospective brides and grooms, one or both of whom have not reached the age requirement in the state regulations as stipulated in the Law. In the latest Marriage Law on Marriage, No. 16 of 2019 reads,